Usage cases: A useful way to improve effectiveness of e-learning web based platforms - Wanzeller, Cristina (2011)
In this paper we propose a more effective use of the e-learning platforms resources, in order to decrease the effort and time required to derive useful knowledge and bringing up together multiple valuable contributions to overcome resource maintenance difficulties. The primary target of our work is the role of a Web based platforms’ administrator (and promoter) that hasn’t enough experience on site optimization and resource maintenance. Our idea to deal with this challenge is to assist such tasks, providing a system that acquires and reuses the knowledge gained from the experience in solving problems concerning administration activities. The system explores the case- based reasoning approach to accomplish its duty of suggesting a suited solution for particular usage data analysis problem, on an e-learning Web based platform, as well, supporting the collecting and structuring of the knowledge contained on successful solved usage problems. We describe the system and propose its application to the specific domain of e-learning Web based platforms optimization. We are specifically engaged in facilitating the collection and cataloguing of knowledge in this area, so it can be shared, evaluated and finally reused in new situations.